Directions for improving the pension indexations mechanism in the context of Russian economy’s transformation - M. L. Dorofeev (Вестник университета)
The purpose of this study is to analyse the current mechanism for indexing pensions of Russian pensioners and find directions for its possible development in the context of the structural transformation of the Russian economy. To achieve this goal, a statistical and coefficient analysis of pension level indicators from the Rosstat database was carried out. Based on the results obtained, it was concluded that, all other things being equal, it is not possible to fundamentally improve the level of pension provision and it is necessary to continue to carry out significant reforms of the Russian pension system. Taking into account the new realities in which Russia found itself after February 2022, authors proposed and analysed directions in which it would be possible to further reform the Russian pension system. The proposed directions were classified into four groups: 1) measures of a general economic nature, indirectly affecting the level of pension provision; 2) changing the general parameters of the existing pension system in order to optimize it; 3) the development of a non-governmental pension insurance system to solve the problem of a low replacement rate for high-income groups of pension recipients and 4) a change in the existing mechanism for indexing pensions, which involves more radical changes to fundamentally increase the level of pension provision for Russian pensioners.